2005
DOI: 10.1007/s00436-004-1285-3
|View full text |Cite
|
Sign up to set email alerts
|

The implantation of Taenia solium metacestodes in mice induces down-modulation of T-cell proliferation and cytokine production

Abstract: The purpose of this study was to determine the effect of the implantation of Taenia solium metacestodes and the treatment with suppressive metacestode factor (F1) on the ability of spleen cells from Balb/c mice to produce cytokines. Cytokine production was estimated 12 days following the implantation or 4 days after the last dose of F1 (five doses) by RT-PCR and flow cytometry analyses. Spleen cells were obtained from metacestode-implanted, F1-treated and control mice. They were stimulated with concanavalin A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…These data contrast with the elevated TNF-α and CXCL8 concentrations detected in a wide range of parasitic diseases (46-49). Data are consistent with other observations indicating that innate and adaptive arms of the host-immune response may be downregulated in response to T. solium (42, 44, 50, 51). In contrast, there was no evidence of immune suppression in Con A-stimulated PBMCs from NCC patients compared with controls (52), and active peripheral immunity was reported in NCC patients (53).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data contrast with the elevated TNF-α and CXCL8 concentrations detected in a wide range of parasitic diseases (46-49). Data are consistent with other observations indicating that innate and adaptive arms of the host-immune response may be downregulated in response to T. solium (42, 44, 50, 51). In contrast, there was no evidence of immune suppression in Con A-stimulated PBMCs from NCC patients compared with controls (52), and active peripheral immunity was reported in NCC patients (53).…”
Section: Discussionsupporting
confidence: 92%
“…Our data are consistent with other findings that showed that T. solium manipulates the host-immune system into supporting its survival by keeping a low-inflammatory profile. Implantation of metacestodes into mice significantly reduced production of IL-2 and IL-4 from CD8 + cells, as well as IFN-γ from CD4 + cells (42). A metacestode-derived factor significantly reduced inflammation and cyst degeneration in an experimental mouse model (43).…”
Section: Discussionmentioning
confidence: 99%
“…implantation of metacestodes of T. solium in mice renders T cells refractory to polyclonal stimulation and inhibits the increase of pro-inflammaroty cytokines [72]. When these parasites are killed by treatment with praziquantel, these immunomodulatory activities are lost, indicating that live parasites are able to modulate host immune responses.…”
Section: Immunomodulation In Cysticercosismentioning
confidence: 99%
“…(2014) identified correlations among T. crassiceps infection, altered short-term memory and altered levels of neurotransmitters and cytokines in the mouse hippocampus. Using T. solium metacestode in vitro secretions obtained from cysticercotic pigs, a ‘fraction’ of low molecular weight has been isolated, which significantly induced down-modulation of human and mouse T-cell proliferation and cytokine production when stimulated with lectins (Molinari et al ., 1990; Arechavaleta et al ., 1998; Hernández-Mendoza et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%